Cloud Computing: The Smart Way to Manage Documents at Educational Institutions - Maharani, Maylinda Putri; Mu’arif, Syamsul (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
The application of cloud computing in archive management in one educational institution has had a significant impact on the efficiency and effectiveness of school administration. This research aims to evaluate the effectiveness of cloud computing in improving accessibility, security, and collaboration in digital records management. This research applies a qualitative method with a case study approach to explore the application of cloud computing as an innovative solution in document management in educational institutions. The results show that the cloud-based system enables faster archive searches, reduces the risk of data loss, and facilitates collaboration between staff. The application of cloud computing in this school also supports the digitization of documents in a structured and secure manner. However, there are challenges in the readiness of human resources, especially in training the use of new technology. Thus, continuous training and mentoring are needed so that the system can be implemented optimally. Overall, cloud computing has proven to be effective in modernizing records management in an educational environment, with a note that increasing user readiness is an important factor in its successful implementation.